Empowering Students with Entrepreneurial Skills and Alternative Income through Guppy Cultivation in the P2MW Program - Amirudin, Muhammad Khoiril; Aisyah, Siti; Riza, Moch Dicky; Prasetyo, Yudy (Universitas Airlangga, 2025)
Entrepreneurial skills are crucial for the younger generation's adaptation to the creative economy. Higher education has a strategic role in producing graduates capable of innovative businesses. The Student Entrepreneurship Development Program (P2MW) aims to strengthen the campus entrepreneurial ecosystem through coaching, mentoring, and training. However, research specifically evaluating P2MW's role in developing student business skills in economically promising sectors like guppy farming is limited. This study examines P2MW's effectiveness in improving entrepreneurial skills among PGRI Delta University students in guppy farming, including technical, managerial, income, impact, and challenges. Using a qualitative case study with interviews, observation, and document analysis of three student participants, the research found that P2MW significantly enhanced entrepreneurial skills, technical knowledge, sustainable income, and economic independence. Results show substantial increases in sales (48%), revenue (34,94%), and guppy variants (400%) through effective hybrid marketing and financial management. The program successfully integrated technical and managerial aspects, creating a replicable business model and sustainable income. This study enriches practice-based entrepreneurship education literature and offers a model for higher education, with potential for replication in other agribusinesses and providing practical program development recommendations. Further research with more participants and longer tracking is suggested.